2020
DOI: 10.4236/aid.2020.101004
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Leptospirosis among Army Personnel in Northeastern Malaysia

Abstract: Leptospirosis is a zoonotic disease caused by pathogenic Leptospira. The disease affects various high-risk groups including army personnel, who are at risk because of field activities that bring them into close contact with zoonotic reservoirs. This cross-sectional study determined the seroprevalence of leptospirosis among 616 asymptomatic army personnel in Northeastern Malaysia. Sociodemographic data were obtained using validated questionnaires. Serological screening for leptospirosis was performed using an E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In this study, seroprevalence was revealed to be greater than that described in other military populations, such as the US military with 4% [10], 16.2% in Malaysia [8], and 8% in Nepal [11], although these studies do not state if their population was working directly with animals. We can compare these results to those of another Mexican population working directly with animals or animal‐related products.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In this study, seroprevalence was revealed to be greater than that described in other military populations, such as the US military with 4% [10], 16.2% in Malaysia [8], and 8% in Nepal [11], although these studies do not state if their population was working directly with animals. We can compare these results to those of another Mexican population working directly with animals or animal‐related products.…”
Section: Discussionmentioning
confidence: 54%
“…The result differs from that reported in another study of militaries in Malaysia, where officials were less affected by Leptospira spp. [8]. The explanation is that this study is focused on a military population that worked in close contact with animals, where the highest rankings are held by veterinarians, and one of their duties is prevention and prophylaxis of livestock diseases and other animals used in the army; thus, they represent the most vulnerable group of this zoonotic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation